A Dynamic Business Model for IT Industries - Berlian, Zainal; Thanh Nguyen, Phong; V. Panyukova, Ekaterina; Laxmi Lydia, E.; Shankar, K. (Opción, 2019)
The business models is summarized into two distinct approach by the static and also the transformational. This aim of proposes a 3rd ap- proach for business, particularly a dynamic approach to business mod- els and the versatile and adaptive of business models is developed more supported the commercial network and structure approach. The busi- ness model is embedded system in business contents and business net- works model, and relies on changes within the business setting. Because of these mutual dependent between business network peoples, and with- in of the recent capabilities and the business models of resources, the business model might also depend upon production and co-production, collect and share, and be utilized by the numerous actors embedded system in worth networks business of IT industries. This differs from the normal read, during which corporations produce worth severally of every different. A network model, flexible, and co-produced business model works a unique tool for business model environments.